2015
DOI: 10.5005/jp-journals-10013-1244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Superior Attachment of Uncinate Process on Presence of Agger Nasi

Abstract: Objective: The superior attachment of uncinate process and agger nasi (AN) cell are important landmark in frontal sinus surgery, and are in close relation to each other. The aim of the study is to investigate the relationship between the superior attach ment of uncinate process (UP) and presence of AN cell. Study design: A retrospective radiological study. Materials and methods: Fifty patients with features of chro nic sinusitis were evaluated radiographically, i.e. computed tomo graphy (CT), 100 sides, i.e. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Literature in other parts of world mentions lamina papyracea attachment between 60-70%, skull base 20-25% and middle turbinate 5-10% [8,9,10] . Indian studies describe lamina papyracea attachment within range of 50% -55%, followed by skull base attachment at 30-40 % and middle turbinate attachment at 10-15% [11] . Prevalence of agger nasi cells were reported in a wide range of 40 to 100% in different studies; these cells are very commonly found during endoscopic surgery as experienced by author.…”
Section: Resultsmentioning
confidence: 99%
“…Literature in other parts of world mentions lamina papyracea attachment between 60-70%, skull base 20-25% and middle turbinate 5-10% [8,9,10] . Indian studies describe lamina papyracea attachment within range of 50% -55%, followed by skull base attachment at 30-40 % and middle turbinate attachment at 10-15% [11] . Prevalence of agger nasi cells were reported in a wide range of 40 to 100% in different studies; these cells are very commonly found during endoscopic surgery as experienced by author.…”
Section: Resultsmentioning
confidence: 99%